2016
DOI: 10.4103/0019-557x.184573
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral health status and oral health-related quality of life among the prison inmate population of kanda model jail, Shimla, Himachal Pradesh, India

Abstract: The prison population is a challenging one with many health problems including oral health. In a country such as India, the information regarding the oral health status in prisoners is scant. So, a cross-sectional study was carried out among a 311 prison inmate population of Kanda model jail, Shimla, Himachal Pradesh, India, to assess the dental caries levels, periodontal health status, and oral health-related quality of life (OHRQoL). Dental caries was present among 71.8% of the population and the mean decaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 0 publications
6
27
1
2
Order By: Relevance
“…The risk of observer bias was detected in 12 of the 34 articles reviewed . This reinforces the importance to use measures aimed at improving diagnostic capacity before and throughout a study.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The risk of observer bias was detected in 12 of the 34 articles reviewed . This reinforces the importance to use measures aimed at improving diagnostic capacity before and throughout a study.…”
Section: Discussionmentioning
confidence: 60%
“…These aspects should be clarified in the methodology, whether by describing the blinding of the evaluator, reporting the previous administration of the questionnaire, delegating another researcher to administer the questionnaire or asking the participants to self‐administer the questionnaire. In some of the studies included in the present review, it was not clear when the quality of life measure was administered . In other studies, the risk of evaluation bias was found .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations